Whipple’s disease - Boris Sergeyevich Belov (Современная ревматология)
Whipple’s disease is a rare multisystemic disease caused by the gram-positive bacillus Tropheryma whipplei. The paper characterizes the etiology and pathogenesis of the disease, gives a broad spectrum of its clinical manifestations, and outlines the basic principles of diagnosis and therapy.